Using remote sensing data to predict road fill areas and areas affected by fill erosion with planned forest road construction: a case study in Kastamonu Regional Forest Directorate (Turkey) - Aricak, Burak (Springer Science and Business Media LLC, 2015)
Forest roads are essential for transport in managed forests, yet road construction causes environmental disturbance, both in the surface area the road covers and in erosion and downslope deposition of road fill material. The factors affecting the deposition distance of eroded road fill are the slope gradient and the density of plant cover. Thus, it is important to take these factors into consideration during road planning to minimize their disturbance. The aim of this study was to use remote sensing and field surveying to predict the locations that would be affected by downslope deposition of eroding road fill and to compile the data into a geographic information system (GIS) database. The construction of 99,500 m of forest roads is proposed for the Kastamonu Regional Forest Directorate in Turkey. Using GeoEye satellite images and a digital elevation model (DEM) for the region, the location and extent of downslope deposition of road fill were determined for the roads as planned. It was found that if the proposed roads were constructed by excavators, the fill material would cover 910,621 m(2) and the affected surface area would be 1,302,740 m(2). Application of the method used here can minimize the adverse effects of forest roads.
Keywords: Satellite Imagery; Turkey; Geographic Information Systems; Transportation; Forests; Ecosystem; Environmental Monitoring; 13. Climate action; 15. Life on land